Pengaruh pemanfaatan media pembelajaran interaktif terhadap minat belajar siswa - Rahmatillah, Zahra (Maliki Interdisciplinary Journal, 2024)
The utilization of interactive learning media has become a very important aspect in the context of learning. The focus of this study is to explore the impact of using interactive learning media on students’ interest in learning. The research method used is a quantitative approach with a quasi-experimental pre-test group design. The research sample consisted of 60 seventh grade students of SMP Negeri 1 Malang who were divided into two groups: the experimental group that used interactive learning media and the control group that did not use the media. Data were collected through learning interest questionnaire and analyzed using tests. The results showed a significant difference in students’ interest in learning between the experimental and control groups after the intervention. This finding confirms that the use of interactive learning media has a positive effect on students’ learning interest.